Assessing and Controlling Acquiescent Responding When Acquiescence and Content Are Related: A Comprehensive Factor-Analytic Approach. Issue 5 (2nd September 2016) - Ferrando, Pere Joan; Morales-Vives, Fàbia; Lorenzo-Seva, Urbano
Abstract : This article proposes procedures for assessing and controlling acquiescence in personality scales when acquiescence is related to the content that the scale intends to measure. Our proposal is comprehensive in that it can be applied to different item response formats fitted with response models that can be parameterized as factor-analytic models. In the calibration stage, our proposal makes joint use of a balanced scale and a set of markers for acquiescence, and consists of 2 sequential procedures: a direct semirestricted solution, and a restricted solution with minimal identification constraints. In the scoring stage, we discuss how the information given by the acquiescence–content relation can be used to obtain Bayes expected a posteriori scores. The robustness of the direct procedure is assessed both analytically and by simulation. A free, user-friendly program that implements the procedures proposed is made available. Practical issues of use and interpretation are discussed and illustrated with an empirical application.